EXPLORING CULINARY DESTINATION IMAGE: PERSPECTIVE RESIDENT AND TOURIST - Irene Veronika Meliani (Politeknik Negeri Bandung, 2018)
The creative economy is currently developing in Indonesia. Culinary is one of the sectors that contribute significantly to the creative economy. These developments have an impact on the increasingly tight competition so that the need for the development of culinary destinations in each region. Competition in the competitive culinary market, business people, need to create an appropriate strategy related to the image of destinations including for Bandung culinary destinations. This research has a purpose of discussing the relationship of destination image (cognitive image and affective image), customer satisfaction, and buying intention. This study uses 414 samples of the population and tourists in Bandung, Indonesia. The result of the research shows that cognitive image and affective image influence consumer's satisfaction, the cognitive image does not affect buying intention and affective image influence buying intention.